Progress of Nuclear Safety for Symbiosis and Sustainability Advanced Digital Instrumentation, Control and Information Systems for Nuclear Power Plants - Yoshikawa, Hidekazu; Zhang, Zhijian (Springer Japan : Imprint: Springer, 2014)
This book introduces advanced methods of computational and information systems, allowing readers to better understand the state-of-the-art design and implementation technology needed to maintain and enhance the safe operation of nuclear power plants. The subjects dealt with in the book are (i) Full digital instrumentation and control systems and human-machine interface technologies, (ii) Risk  monitoring methods for large and  complex  plants, (iii) Condition monitors for plant components, (iv) Virtual and augmented reality for nuclear power plants, and (v) Software reliability verification and validation for nuclear power plants. The target readers of this book are Ph.D. students, researchers, and engineers in the field of nuclear power engineering.  .